2018
DOI: 10.1017/s0268416018000164
|View full text |Cite
|
Sign up to set email alerts
|

Pre-industrial welfare between regional economies and local regimes: rural poor relief in Flanders around 1800

Abstract: This study uses data on income and distribution of relief payments from local poor relief tables for 512 rural parishes in Flanders (present-day Belgium) in 1807 to examine spatial variation in poor relief practices in a region characterised by well-established local poor relief institutions and marked socio-economic differences. By combining data on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They claim therefore that in early modern Flanders and Brabant different roles were assigned to poor relief: as an instrument for labour regulation or one for social cohesion. 12…”
Section: Large-scale Data Collectionmentioning
confidence: 99%
“…They claim therefore that in early modern Flanders and Brabant different roles were assigned to poor relief: as an instrument for labour regulation or one for social cohesion. 12…”
Section: Large-scale Data Collectionmentioning
confidence: 99%
“…31 This is relatively high compared to the pauper population spectrum, as an 1808 enquiry into poor relief showed that most parishes had a share of 4.5 per cent to 12 per cent of the population dependent on poor relief. 32 We should however note that Bulskamp, a little polder village with fertile land suitable for arable farming and pasture, does not represent the entirety of the Coastal Flanders area. Great diversity existed between these parishes, let alone between other regions in the economically and ecologically more diverse area of the Concordat.…”
Section: The Concordat Of Ypres: Resolving Relief Issues Locallymentioning
confidence: 99%
“…Prosperity in this case depended mainly on natural conditions. The policy measures were implemented on a local and regional scale [12]. In the first phase of the industrial society, the Industrial Revolution gradually brought industrial technology and market relations to the countryside.…”
Section: Introduction: Declining Rural Regions In the Context Of Cont...mentioning
confidence: 99%